An intelligent digital guide plate for visual inspection of seating and dynamic balance - Zhao, Xiang-Zhe; Shi, Nai-Yu; Chen, Qian; Xing, Yue; Guo, Yan-Zhu; He, Ming-Zhu; Song, Fu-Xiang; Liu, Bin (Frontiers in Materials, 2025)
The aim of the present study was to develop an intelligent digital planting guide plate to achieve precise positioning and dynamic balance of the guide plate with visual real-time monitoring. To achieve this, Mechanoluminescence (ML) materials (BaSi2O2N2: Eu2+, BSON) was innovatively incorporated into methyl methacrylate (MAA) resin, forming BM composite materials with varying BSON doping concentrations (2 wt%, 4 wt%, 8 wt%, 16 wt% and 32 wt%) using mechanical blending, after 3D printing MMA was changed to Polymethyl methacrylate (PMMA). The intelligent guide plate was successfully fabricated via 3D printing technology, followed by a randomized clinical trial involving 50 patients. The successful integration of BSON into MAA was confirmed through scanning electron microscopy (SEM), X-ray diffraction (XRD), Fourier-transform infrared spectroscopy (FTIR), and X-ray photoelectron spectroscopy (XPS). Notably, the BM4 composite exhibited significantly enhanced mechanical properties, with an increase of 353.81% in elastic modulus, 64.52% in load-bearing capacity, and 70.19% in bending strength compared to pure PMMA. Additionally, BM4 demonstrated superior hydrophilicity and exceptional biocompatibility. Further, BM4 displayed pronounced mechanoluminescence in response to mechanical stress. The clinical accuracy of BM composite material intelligent guide plate was validated through a clinical study involving 50 patients implant placement with BM composite surgical guides. There was no significant difference between the BM composite material intelligent guide plate and the traditional guide plate, confirming its clinical feasibility. This study provides a precise and minimally invasive solution for oral implant restoration and is of significant importance in advancing the development of digital medical technology.